Osmoregulation in Saccharomyces cerevisiae Studies on the osmotic induction of glycerol production and glycerol 3-phosphate dehydrogenase (NAD+) - André, Lars; Hemming, Anna; Adler, Lennart (FEBS letters, 1991)
Production of glycerol and a key enzyme in glycerol production, glycerol 3-phosphate dehydrogenase (NAD+) (GPD), was studied in Saccharomyces cerevisiae cultured in basal media or media of high salinity, with glucose, raffinose or ethanol as the sole carbon source. At high salinity, glycerol production was stimulated with all carbon sources and glycerol was accumulated to high intracellular concentration in cells grown on glucose and raffinose. Cells grown on ethanol accumulated glycerol to a lower level but showed an increased content of trehalose at high salinity. However, the trehalose concentration corresponded only to about 20% of the glycerol level, and did not compensate for the shortfall in intracellular osmolyte content. Immunoblot analysis demonstrated an increased production of GPD at high salinity. This increase was osmotically mediated but was lower when glycerol was substituted for NaCl or sorbitol as the stress-solute. The enzyme also appeared to be subject to glucose repression; the specific activity of GPD was significantly lower in cells grown on glucose, than on raffinose or ethanol.